Ministry of Religion Communication Techniques in Efforts to Disseminate Halal Certification Obligations for Business Actors in Deliserdang Regency - Mhd Latif Kahfi (Faculty of Law, Universitas Pekalongan, 2023)
This article uses qualitative methods or field research in the form of exposing field facts related to the communication patterns of religious ministries in Deliserdang Regency. This research was conducted at the Office of the Ministry of Religion, Deliserdang Regency, North Sumatra Province. This research was conducted for 6 (six) months in 2023 starting from July to February 2024. The number of informants for this research was 6 (six) people. The data collection technique uses triangulation (observation-interview and documentation). Then the data analysis technique, researchers used the Miles and Huberman model technique with three analysis steps, namely data reduction, data presentation and conclusion drawing or verification. The research results provide an illustration that the use of communication techniques by the Deli Serdang Ministry of Religion in efforts to disseminate halal certification obligations: 1) Informative Communication Techniques, 2) Persuasive Communication Techniques, 3) Human Relations Communication Techniques. To support halal certification activities, the Deli Serdang Ministry of Religion uses various communication media, including: First, Interpersonal Media. Second, Mass Media and Third, Social Media. Then in an effort to disseminate halal certification obligations for business actors in Deliserdang Regency. Implementation must prioritize communication principles and ethics that are in accordance with religious values, integrity and transparency